Scandcleft randomised trials of primary surgery for unilateral cleft lip and palate: 4. Speech outcomes in 5-year-olds - velopharyngeal competency and hypernasality. Issue 1 (2nd January 2017) - Lohmander, Anette; Persson, Christina; Willadsen, Elisabeth; Lundeborg, Inger; Alaluusua, Suvi; Aukner, Ragnhild; Bau, Anja; Boers, Maria; Bowden, Melanie; Davies, Julie; Emborg, Berit; Havstam, Christina; et al.
Abstract: Background and aim: Adequate velopharyngeal function and speech are main goals in the treatment of cleft palate. The objective was to investigate if there were differences in velopharyngeal competency (VPC) and hypernasality at age 5 years in children with unilateral cleft lip and palate (UCLP) operated on with different surgical methods for primary palatal repair. A secondary aim was to estimate burden of care in terms of received additional secondary surgeries and speech therapy. Design: Three parallel group, randomised clinical trials were undertaken as an international multicentre study by 10 cleft teams in five countries: Denmark, Finland, Sweden, Norway, and the UK. Methods: Three different surgical protocols for primary palatal repair were tested against a common procedure in the total cohort of 448 children born with a non-syndromic UCLP. Speech audio and video recordings of 391 children (136 girls, 255 boys) were available and perceptually analysed. The main outcome measures were VPC and hypernasality from blinded assessments. Results: There were no statistically significant differences between the prevalences in the arms in any of the trials. VPC: Trial 1, A: 58%, B: 61%; Trial 2, A: 57%, C: 54%; Trial 3, A: 35%, D: 51%. No hypernasality: Trial 1, A: 54%, B: 44%; Trial 2, A: 47%, C: 51%; Trial 3, A: 34%, D: 49%. Conclusions: No differences were found regarding VPC and hypernasality at age 5 years after different methods for primary palatal repair. The burden of care in terms of secondary pharyngeal surgeries, number of fistulae, and speech therapy visits differed. Trial registration: ISRCTN29932826.